O precedente vinculante e sua eficácia temporal no sistema processual brasileiro - Ataíde Júnior, Jaldemiro Rodrigues de (2011)
This study aims to demonstrate that the development of the legal traditions of civil law and common law was strongly determined by the historical context present in French and England, respectively, which influenced the idolatry of the law, in the first system, and the respect of the stare decisis, in the second; however, with the approach of these two large families due to the crises of modernity, of constitutionalism and other relevant factors, it is necessary to adopt the binding precedent in civil law, in order to provide greater security and predictability in the achievement of the law. We can also observe that the Brazilian Law has been moving towards the system of binding precedent for nearly two decades; but that does not mean that the new model is fully implemented. Thus, it is essential to systematize the temporal effectiveness of the precedents, especially those that announce a new legal rule, in order to avoid the disrespect of the non-retroactivity of the law, of the legal security, predictability, non-surprise, fair confidence and objective good-faith, exactly the values that we intend to protect with the binding precedents. That means, with the mentioned systematization of the temporal efficacy we try to avoid that the retroactive application of the new precedents ends up denying the very basis of the stare decisis